Unconscionable call of performance bond - Wan Nik, Wan Noor Solehha (2013)
Performance bond is one of the important provisions in construction contracts. The provision requires the contractor to give the employer security for the due performance of the contract. There are two types of performance bond. The first type is called conditional bond. It is a contract guarantee whereby the surety becomes liable upon proof of breach of the terms of the main contract by principal and the beneficiary sustaining loss as a result of such a breach. The second type is unconditional or ‘ondemand’ performance bond. It is a covenant whereby the surety becomes liable merely when a demand is made upon him by the beneficiary with no necessity for the beneficiary to prove any default by the principal in performance of the main contract. The main distinction between the two types of bond is with respect to the requirement for making call on the bond. In conditional performance bond, the beneficiary must comply with conditions precedent for calling the bond. In unconditional bond, the only condition precedent is a written notice to the surety. However, the contractor may apply for injunction against the employer to restrain the employer from calling the bond or receiving any payment under the performance bond. When considering the application for injunction, the courts have to determine the presence of fraud or unconscionable conduct by the employer. In most court cases, unconscionability had been interpreted as unfairness. In determining unconscionability, the court will use the test of ‘balance of convenience’ and ‘seriously arguable and realistic inference test’. However, whether there is unconscionability depends on the facts of each case. There is no predetermined categorization. The court has to assess the whole facts of the cases to determine unconscionability. From the court cases, it can be concluded that there are two circumstances that amount to unconscionable conduct. Firstly, breach of contract by the contractor that is induced by employer’s own default such as late payment and secondly, force majeure such as typhoon and flood.